(untitled) (Research, Society and Development, 2021)
This research aims to evaluate the application of the methodology of problematization in the theoretical and practical teaching of Nursing Fundamentals II. This is a descriptive study with a qualitative approach, having as study participants the students enrolled in the discipline of Nursing Fundamentals of the Aurora de Afonso Costa Nursing School - EEAAC/UFF, in the 2nd semester of 2014 and the teachers of this same discipline. Hybrid content analysis was performed. After data analysis, these were divided into three categories: teacher education and didactics applied in higher education; the curriculum of the nursing course: fundamental skills for the professional training of the future nurse; the use of them etiologic of problematization in higher education, to discuss about possible changes and how they would be carried out, taking into account professional competencies, the importance of the relationship between nurse and patient and nursing practices as whole, through the training of students with more power of reflection, criticism and technical capacity. The new methodological approach of problematization allowed the student to clearly understand the competencies of the nurse and how they can be used in their professional routine. This methodological application served as a substantial method to be applied in the discipline, and the teacher can expand the content and work on issues related to problematization nursing care and professional education. Despite all the changes already underway, the methodology of problematization still represents a challenge nowadays of higher education.